Living and Learning as Māori: Language Stories from Three Generations - Tocker, Kimai (The Australian Journal of Indigenous Education, 2017)
Through tracing in detail the story of schooling for three individuals, this article provides a rich description of the way that education impacted on the lives of many Māori between the early 1900s and the year 2000. Although there is extensive research on the historical colonising effects of schooling on Māori and te reo Māori (the Māori language), this article approaches these effects by bringing them alive and illustrating them in the everyday lived experience of women from three generations: my mother, myself, and my daughter. Through this method, the article maps in evocative detail the important historical period between the banning of Māori language in schools and the renaissance of Māori language teaching and speaking in schools.